2009
DOI: 10.1111/j.1365-2230.2009.03238.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant tumour of the heel: acquired fibrokeratoma

Abstract: Fibrokeratoma is a rare benign invasive tumour usually located on the digits. We report a 35-year-old patient with a giant acquired fibrokeratoma of the heel. Despite its large size and unusual location, the tumour was microscopically benign and was successfully excised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 8 publications
1
16
0
4
Order By: Relevance
“…The most common locations are the fingers and toes near the interphalangeal joints, and the tumors generally measure <1 cm . By contrast with the eight cases of giant ADFK reported so far, in which the areas involved were the heel or toes, we report a case of giant ADFK of the finger.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…The most common locations are the fingers and toes near the interphalangeal joints, and the tumors generally measure <1 cm . By contrast with the eight cases of giant ADFK reported so far, in which the areas involved were the heel or toes, we report a case of giant ADFK of the finger.…”
mentioning
confidence: 71%
“…Although the exact pathophysiology of ADFK is unknown, repetitive trauma, collagen neoformation by fibroblasts, and Factor XIIIa are reported to play important roles . Differential diagnoses of ADFK include cutaneous horn, verruca vulgaris, supernumerary digit, Koenen's tumor, and inclusion body fibromatosis . The distinguishing characteristic of ADFK is the presence of a collarette of slightly raised skin called a “moat”, which encircles the lesion .…”
mentioning
confidence: 99%
“…Additionally, one case in which ADFK presented as a cluster of multiple plantar nodules has been described . ADFK occurs primarily in adult males with an age range of 39–77, though cases of female adults have also been reported . It has been reported in patients from different ethnicities and racial backgrounds, as reported in German, Polish, Japanese, French, and Indian literature …”
Section: Clinical Presentation and Epidemiologymentioning
confidence: 99%
“…ADFK is typically asymptomatic and occurs as a solitary, flesh‐colored papule or nodule less than 1 cm in diameter (Fig. ), but less commonly it may present as a symptomatic nodule much larger than 1 cm and can cause significant pain, also known as giant acquired digital fibrokeratoma . It most commonly occurs on the fingers but can also be seen on the palm, toes, and sole .…”
Section: Clinical Presentation and Epidemiologymentioning
confidence: 99%
“…found that 90% of lesions occurred on the digits, and the male to female ratio was 29 to 21. Exceptionally, fibrokeratomas appeared on the elbows, wrists, pre‐patellar region, calves, and heels . Despite the lack of a consensus, fibrokeratomas greater than 1 cm in diameter have been reported as giant fibrokeratomas, and lesions up to 7 × 5 × 1.1 cm have been reported …”
Section: Introductionmentioning
confidence: 99%